2011
DOI: 10.1007/s11205-011-9826-5
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Specific Life Satisfaction Domains and Disordered Eating among College Students

Abstract: This thesis examines the relationship between life satisfaction (e.g., family, friends, etc.) and eating behaviors/weight perceptions of 723 college students. Participants completed the survey and data were analyzed using correlations and logistic and multinomial regressions (genders analyzed separately). Satisfaction with Self and Physical Appearance were the strongest correlates with eating variables (-.528 to .369). Worrying about weight (-.528 to-.104), selfdescribed weight (-.407 to-.129), and binging (.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 102 publications
3
21
0
3
Order By: Relevance
“…Other studies found similar results concerning the prediction of this variable based on satisfaction with life (Matthews et al, 2012). Nevertheless, because drive for thinness is usually related to a risk of eating disorders in women (Garner, 1991), the importance of satisfaction with life seems to be limited for the prevention of risk in female adolescents and other protective factors should be targeted in prevention programs to modify preoccupation with weight and the intense fear of gaining weight.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Other studies found similar results concerning the prediction of this variable based on satisfaction with life (Matthews et al, 2012). Nevertheless, because drive for thinness is usually related to a risk of eating disorders in women (Garner, 1991), the importance of satisfaction with life seems to be limited for the prevention of risk in female adolescents and other protective factors should be targeted in prevention programs to modify preoccupation with weight and the intense fear of gaining weight.…”
Section: Discussionmentioning
confidence: 71%
“…Satisfaction with life has been negatively related to several eating disorder-related symptoms, such as vomiting, perception of being overweight, binge eating behavior (Matthews, Zullig, Ward, Horn, & Huebner, 2012;Zullig, Pun, & Huebner, 2007), dieting, laxative use (Esch & Zullig, 2008;Valois, Zullig, Huebner, & Drane, 2003), perceived eating control (Greeno, Jackson, Williams, & Fortmann, 1998), and body dissatisfaction (Brannan & Petrie, 2011), in college students, eating disorder patients, younger and older adolescents, and adults. These associations have been particularly strong for female subjects.…”
Section: Satisfaction With Lifementioning
confidence: 99%
“…8 Based on our regression results, it can be calculated that for a student with one child below 7 and one child between 7 and 13, the estimated satisfaction score is 5.10 for males and 5.35 for females, ceteris paribus (all other variables at the sample means).…”
Section: Regression Resultsmentioning
confidence: 99%
“…Similar methods can be used to examine even more peculiar issues; see e.g., Matthews et al [8] who explore the relationship between specific domains of satisfaction and disordered eating. 2 In most of the total life satisfaction studies, education has traditionally been viewed as a domain of life satisfaction.…”
Section: Variables and Datamentioning
confidence: 99%
“…Ces associations n'établissent pas de lien de cause à effet entre la satisfaction des élèves à l'égard de la vie et le fait qu'ils mangent le matin et le soir (ni de relation directe, car d'autres facteurs peuvent influer à la fois sur la satisfaction des élèves à l'égard de la vie et leurs habitudes alimentaires), mais elles confirment la thèse qu'à l'adolescence, troubles alimentaires et faible satisfaction à l'égard de la vie peuvent être fortement liés (Matthews et al, 2012 Dans la plupart des économies industrialisées, être en bonne santé est un idéal, mais la minceur est souvent un canon de beauté. Ce message brouillé est parfois à l'origine d'une obsession du poids qui peut être particulièrement éprouvante à l'adolescence.…”
Section: Les Habitudes Alimentaires Des éLèves Et Leur Bien-êtreunclassified